Loss characteristic negative temperature coefficient integrated inductor and preparation method thereof
By passivating, covering and heat treatment of carbonyl iron powder and aerosolized iron nickel powder, a high permeability central column and coil are formed, solving the problem of increased loss of the integrated molded inductor at high temperatures, and achieving high inductance and low inductance Comprehensive effect of loss.
Patent Information
- Application Number
- CN202411768047.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The problem of the increase in the loss of existing integrated molded inductors at high temperatures makes it difficult to achieve high inductance and low loss at the same time.
The preparation method of soft magnetic metal powder is adopted, including passivation, coating, granulation and adding lubricant to the carbonyl iron powder and aerosolized iron nickel powder, forming a high magnetic permeability center column and coil, and passing through stages Heat treatment and pressing process form an integrated molded inductor with negative temperature coefficient of loss characteristics.
It realizes the maintenance of inductance value and the reduction of loss at high temperatures, improves the inductance value and magnetic permeability, and ensures the moldability and low loss performance of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic functional materials, and in particular relates to an integrally formed inductor with a negative temperature coefficient of loss characteristics and a preparation method thereof. Background Art
[0002] As an important component of electronic products, new electronic components are developing in the direction of chip-type, miniaturization, high frequency, broadband, high precision, integration and green environmental protection, which puts forward higher requirements on the size and performance of power inductor products, requiring them to have the characteristics of small size, large current, low power consumption, high magnetic shielding effect, high product uniformity, etc. Therefore, the outside world pays more and more attention to one-piece molded inductors. One-piece molded inductors are made by burying the wound copper coil in metal powder and die-casting. Due to the high degree of mechanization and the use of more automated equipment in the production process, the production efficiency is much higher than that of traditional inductors, and the product performance is uniform and the stability is good. However, with the expansion of the use environment and usage requirements, the disadvantages of one-piece molded inductors such as low inductance and increased high-temperature losses have become increasingly obvious. This is because there is a wound coil inside the one-piece molded inductor. Excessive molding pressure will cause the coil to deform or short-circuit, making it impossible to use high-pressure pressing to mold the one-piece molded inductor, which means that the metal powder cannot be compacted, and the lower density brings lower magnetic permeability, and the product cannot obtain high inductance; and the conventional materials for preparing one-piece molded inductors, such as carbonyl iron, iron silicon chromium, etc., all increase in loss with increasing temperature. Therefore, how to improve the inductance value of the one-piece molded inductor and reduce the loss of the one-piece molded inductor at high temperature still needs to be solved.
[0003] Patent publication number CN116246879A discloses a method for preparing an integrally formed inductor using amorphous powder, which aims to improve the magnetic permeability through the use and treatment of amorphous powder. However, amorphous powder has high strength and is difficult to compress, and the magnetic permeability of amorphous powder itself is low and extremely difficult to improve. Therefore, the goal of high magnetic permeability and high inductance is difficult to achieve. Patent publication number CN113380505A discloses a method of organic and inorganic composite coating to reduce losses and prepare integrally formed inductors, but it still cannot change the problem that losses increase with increasing temperature.
[0004] Therefore, it is very necessary to develop an integrated inductor with a negative temperature coefficient of loss characteristics and a preparation method thereof. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a loss characteristic negative temperature coefficient one-piece molded inductor and a preparation method thereof, which not only has the advantage of high inductance value, but also has the advantage of reduced loss as temperature increases.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: The present invention provides a method for preparing a loss characteristic negative temperature coefficient integrally formed inductor, comprising the following steps: (1) Preparation of soft magnetic metal powder: The carbonyl iron powder and the atomized iron-nickel powder are respectively subjected to passivation, coating, granulation and lubricant addition treatment to obtain two soft magnetic metal powders: the treated carbonyl iron powder and the treated atomized iron-nickel powder, which are used for standby; (2) Preparation of the one-piece molded inductor center column: The treated gas-atomized iron-nickel powder is pressed to form the center column of the one-piece molded inductor, and then heat-treated; (3) Bonding the center column into the coil; (4) The coil bonded in step (3) is embedded in the treated carbonyl iron powder, pressed into shape and baked to obtain a product.
[0007] Preferably, in step (1), the specific processing methods of passivation, coating, granulation and adding lubricant are: (1-1) Passivation: The carbonyl iron powder is passivated by using suspension A; the atomized iron-nickel powder is passivated by using suspension B; The suspension A comprises: phosphoric acid, aluminum zinc phosphomolybdate, manganese zinc ferrite powder and distilled water; The suspension B comprises: phosphoric acid, aluminum zinc phosphomolybdate, manganese zinc ferrite powder, chromic acid and distilled water; (1-2) Coating: The coating liquid used during coating is an acetone solution containing phenylchlorosilane, methylchlorosilane, silicone resin, and silane coupling agent; (1-3) Granulation: The coated carbonyl iron powder is granulated into 60 mesh, and the coated aerosolized iron-nickel powder is granulated into 100 mesh; (1-4) adding a lubricant: mixing the lubricant with the granulated carbonyl iron powder and the granulated atomized iron-nickel powder, respectively, to obtain treated carbonyl iron powder and treated atomized iron-nickel powder; Preferably, in step (1-1) of step (1), in the suspension A, the mass of phosphoric acid is 0.1-0.3% of the mass of the carbonyl iron powder, the mass of aluminum zinc phosphomolybdate is 0.3-0.5% of the mass of the carbonyl iron powder, the mass of manganese zinc ferrite powder is 0.1-0.2% of the mass of the carbonyl iron powder, and the mass of distilled water is 15-30% of the mass of the carbonyl iron powder; In the suspension B, the mass of phosphoric acid is 0.1-0.3% of the mass of the atomized iron-nickel powder, the mass of aluminum zinc phosphomolybdate is 0.3-0.5% of the mass of the atomized iron-nickel powder, the mass of manganese zinc ferrite powder is 0.1-0.2% of the mass of the atomized iron-nickel powder, the mass of chromic acid is 0.1-0.2% of the mass of the atomized iron-nickel powder, and the mass of distilled water is 15-30% of the mass of the atomized iron-nickel powder; Preferably, in step (1-1) of step (1), the mass ratio of carbonyl iron powder to atomized iron-nickel powder is 1:1; the particle size of carbonyl iron powder is D50=10 μm, the particle size of atomized iron-nickel powder is D50=15 μm; the particle size of manganese-zinc ferrite powder is D50=1 μm; Preferably, in step (1-2) of step (1), when the passivated carbonyl iron powder is coated, in the coating solution, the mass of phenylchlorosilane is 0.5-0.8% of the mass of the carbonyl iron powder, the mass of methylchlorosilane is 0.4-1.0% of the mass of the carbonyl iron powder, the mass of the silicone resin is 2.3-3.5% of the mass of the carbonyl iron powder, and the mass of the silane coupling agent is 0.2-0.3% of the mass of the carbonyl iron powder; the mass of the acetone solution is 8-10% of the mass of the carbonyl iron powder; When the passivated atomized iron-nickel powder is coated, in the coating liquid, the mass of phenylchlorosilane is 0.5-0.8% of the mass of the atomized iron-nickel powder, the mass of the methylchlorosilane is 0.4-1.0% of the mass of the atomized iron-nickel powder, the mass of the silicone resin is 2.3-3.5% of the mass of the atomized iron-nickel powder, and the mass of the silane coupling agent is 0.2-0.3% of the mass of the atomized iron-nickel powder; the mass of the acetone solution is 8-10% of the mass of the atomized iron-nickel powder; Preferably, in step (1-4) of step (1), the lubricant is any one or more of magnesium stearate, zinc stearate, stearic acid, and paraffin powder; Preferably, in step (1-4) of step (1), when a lubricant is added to the granulated carbonyl iron powder, the mass of the lubricant is 0.3-0.4% of the mass of the carbonyl iron powder; When lubricant is added to the atomized iron-nickel powder after granulation, the mass of the lubricant is 0.3-0.4% of the mass of the atomized iron-nickel powder; Preferably, in step (2), the pressing pressure is 1800-2200 MPa; the diameter and height of the middle column after pressing are smaller than the coil, so that the middle column is bonded to the center of the coil; the middle column after pressing is heat treated in a hydrogen atmosphere; Preferably, in the step (3), the coating liquid used during coating is used for bonding treatment; Preferably, in step (2), the heat treatment process includes four insulation stages: the insulation temperature of the first stage is 350-380°C, and the insulation time is 20-30min; the insulation temperature of the second stage is 520-540°C, and the insulation time is 20-30min; the insulation temperature of the third stage is 600-630°C, and the insulation time is 30-50min; the insulation temperature of the fourth stage is 720-730°C, and the insulation time is 50-70min, and finally the furnace is cooled to room temperature; Preferably, in step (4), the pressing pressure is 1800-2200 MPa; the baking process includes two stages: the first stage is to heat up to 120°C for 20 minutes and keep warm for 30 minutes; the second stage is to heat up to 180°C for 20 minutes and keep warm for 150 minutes, and finally cool to room temperature in the furnace.
[0008] The present invention provides an integrally formed inductor with a negative temperature coefficient of loss characteristics, and the integrally formed inductor with a negative temperature coefficient of loss characteristics is prepared by the preparation method.
[0009] The technical solution of the present invention achieves the following beneficial technical effects: The present invention uses carbonyl iron powder and atomized iron-nickel powder in combination, and reasonably limits the raw material composition and dosage of the passivation material and the coating material. The atomized iron-nickel powder is used as the inductor center column, and a staged heat treatment process is adopted to obtain an integrally formed inductor. The integrally formed inductor has a high inductance value, and its loss does not increase with the increase of temperature. Its conversion efficiency at 100°C is higher than that at 25°C, and it has the characteristics of high inductance and negative temperature coefficient of loss. The specific analysis is as follows.
[0010] 1. The present invention combines the manufacturing process of the one-piece molded inductor with the high-pressure pressing and heat treatment stress relief process of the metal magnetic powder core, so that the center column of the one-piece molded inductor has high magnetic permeability and low loss performance, and greatly improves the inductance value of the one-piece molded inductor under the condition of using coils of the same or similar specifications.
[0011] 2. The passivation materials of carbonyl iron used in the present invention are phosphoric acid, aluminum zinc phosphomolybdate, and manganese zinc ferrite powder. This is because the carbonyl iron has a high surface activity. During the passivation process, phosphoric acid provides acidity, which can not only react with the powder to generate iron phosphate substances, but also promote the reaction of aluminum zinc phosphomolybdate and carbonyl iron to generate high resistivity complexes such as aluminum zinc phosphomolybdate iron, which are coated on the surface of the powder, greatly improving the insulation resistance of the powder, thereby reducing eddy current loss and then reducing total loss. Gas atomized iron-nickel powder is difficult to passivate because it contains 50% mass fraction of nickel elements, so adding strongly oxidizing chromic acid as an oxidant can effectively improve the passivation effect. Manganese zinc ferrite powder has certain insulation resistance performance and certain magnetism, so adding manganese zinc ferrite powder is also an effective means to improve magnetic permeability and reduce loss.
[0012] 3. After pressing the center column and the pressed product, the present invention performs heat treatment or baking. The present invention is set to heat up in a curve, which can effectively avoid problems such as product cracking and delamination caused by uneven thermal expansion coefficient during continuous heating of the product, thereby greatly improving the qualified rate of the product.
[0013] 4. The middle column material used in the present invention is atomized iron-nickel powder. The atomized iron-nickel material has the advantages of high density, high saturation magnetic induction intensity, etc. Therefore, the pressed middle column can obtain higher magnetic permeability and optimal DC superposition characteristics under the premise of a certain volume. At the same time, the atomized iron-nickel material is insulated and coated with the formula of the present invention, and its loss performance decreases with increasing temperature. Therefore, during the use of the one-piece molded inductor, as the self-heating and the increase of ambient temperature, the atomized iron-nickel material can reduce the loss, that is, achieve a negative temperature coefficient of loss characteristics.
[0014] 5. The carbonyl iron material used in the present invention has the advantages of high density, good superposition and low loss compared to traditional iron-silicon-chromium materials, and has the advantage of high magnetic permeability compared to amorphous nanocrystalline powders, and can effectively ensure the performance of high inductance and low loss. At the same time, the use of atomized iron-nickel powder gives the obtained inductor the advantage of a negative temperature coefficient, but there is a problem of poor formability when the iron-nickel powder is pressed into products. Therefore, the present invention uses carbonyl iron and atomized iron-nickel powder in combination, which not only meets the negative temperature coefficient, but also ensures the formability of the product or device.
[0015] 6. The coating material of the present invention uses phenylchlorosilane, methylchlorosilane, silicone resin, and acetone solution of silane coupling agent. The combination of several resins has high strength and ensures the bonding strength after the powder is pressed. The greater advantage is that the silane contained in the several resins has good thermal stability. The pressed one-piece molded inductor is used at less than 180°C without the problem of inductance value fluctuation. After the middle column is heat treated at more than 700°C, silane will decompose into silicon dioxide, which still exists between the powder and the powder particles. Silicon dioxide has a high resistivity and can reduce the eddy current loss between the powders, thereby reducing the total loss and achieving the purpose of low loss. DETAILED DESCRIPTION
[0016] The following describes in detail a loss characteristic negative temperature coefficient integrated inductor and a preparation method thereof through specific embodiments of the present invention.
[0017] The raw materials used in the embodiments of the present invention are: aerosolized iron-nickel powder: model: Hi-Flux; manufacturer: Antai Technology Co., Ltd. Aluminum zinc phosphomolybdate: manufacturer: Guangxi Xinjing Technology Co., Ltd. Manganese zinc ferrite: model: TP5H; manufacturer: Tiantong Holdings Co., Ltd. Silane coupling agent: model: 3-glycidyloxypropyltrimethoxysilane; manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0018] In addition to the raw materials described above, the other raw materials mentioned in the present invention can be purchased from domestic and foreign commercial channels and will not be described one by one here.
[0019] Example 1 This embodiment relates to a method for preparing a one-piece molded inductor with a negative temperature coefficient of loss characteristics, comprising the following steps: (1) Preparation of two soft magnetic metal powders: (1-1) Passivation: 100 g of carbonyl iron powder with a D50 of 10 μm was added with a suspension prepared by adding 0.1 g of phosphoric acid, 0.3 g of aluminum zinc phosphomolybdate, 0.1 g of manganese zinc ferrite powder with a D50 of 1 μm, and 20 g of distilled water, and the mixture was stirred for passivation. After drying, the passivated carbonyl iron powder was obtained. 100 g of aerosolized iron-nickel powder with D50=15 μm was added with a suspension prepared by 0.1 g of phosphoric acid, 0.3 g of aluminum zinc phosphomolybdate, 0.1 g of manganese-zinc ferrite powder with D50=1 μm, 0.1 g of chromic acid, and 20 g of distilled water, and stirred for passivation, and dried to obtain a passivated aerosolized iron-nickel powder; (1-2) Coating: using a coating solution containing 0.5 g of phenylchlorosilane, 0.6 g of methylchlorosilane, 2.5 g of silicone resin, 0.2 g of silane coupling agent, and 10 g of acetone solution, the passivated carbonyl iron powder and the passivated atomized iron-nickel powder are respectively coated to obtain coated carbonyl iron powder and coated atomized iron-nickel powder; (1-3) Granulation: The coated carbonyl iron powder is granulated into 60 mesh, and the coated aerosolized iron-nickel powder is granulated into 100 mesh; (1-4) Adding lubricant: 0.3 g of magnesium stearate lubricant is mixed evenly with the granulated carbonyl iron powder to obtain treated carbonyl iron powder; 0.3 g of magnesium stearate lubricant is mixed evenly with the granulated aerosolized iron-nickel powder to obtain treated aerosolized iron-nickel powder; (2) Preparation of the one-piece molded inductor center column: The treated gas atomized iron-nickel powder is used to press the middle column for the one-piece inductor, the diameter of the middle column is 2.78mm, the height is 2.0mm, the use pressure is 2000MPa, and heat treatment is performed. The heat treatment curve is as follows: the first stage insulation temperature is 350℃, the insulation time is 25min; the second stage insulation temperature is 530℃, the insulation time is 25min; the third stage insulation temperature is 620℃, the insulation time is 30min; the fourth stage insulation temperature is 720℃, the insulation time is 60min, and finally cooled to room temperature with the furnace; (3) Using the coating liquid prepared in step (1), the middle column obtained in step (2) is bonded to the center of the one-piece molded inductor coil, the coil specification wire diameter is 0.45 mm, the coil diameter is 2.8 mm, and the number of coil turns is 5.5 turns; (4) The coil bonded in step (3) is embedded in the carbonyl iron powder treated in step (1), and a 0630 series inductor product is pressed at a pressure of 2000 MPa, i.e., an integrated inductor with a length of 6.6 mm, a width of 6.6 mm, and a height of 3.0 mm. After pressing, the product is baked. During the baking process, the first stage is to heat the product to 120° C. for 20 minutes and keep the temperature for 30 minutes; the second stage is to heat the product to 180° C. for 20 minutes and keep the temperature for 150 minutes, and then cool the product to room temperature with the furnace.
[0020] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, the carbonyl iron powder with D50=10 μm and the atomized iron-nickel powder with D50=15 μm used in step (1-1) of step (1) of Example 1 are all replaced with carbonyl iron powder with D50=15 μm (that is, the column material and the embedded material in this comparative example are both carbonyl iron powder). The other steps and parameters are the same as those in Example 1.
[0021] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, the carbonyl iron powder with D50=10μm and the atomized iron-nickel powder with D50=15μm used in step (1-1) of step (1) of Example 1 are all replaced with iron-silicon-chromium powder with D50=13um (that is, the column material and the embedded material in this comparative example are both iron-silicon-chromium powder). The other steps and parameters are the same as those in Example 1.
[0022] Comparative Example 3 The difference between this comparative example and Example 1 is that the passivation agent used in the passivation treatment in step (1) of this comparative example is only 1.0 g of pure phosphoric acid in 20 g of distilled water. The other steps and parameters are the same as those in Example 1.
[0023] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, the gas-atomized iron-nickel powder with a D50 of 15 μm (i.e., the material to be used as the center column) used in step (1-1) of step (1) of Example 1 is replaced with a gas-atomized iron-silicon-aluminum material with a D50 of 18 μm. The other steps and parameters are the same as those in Example 1.
[0024] Comparative Example 5 The difference between this comparative example and Example 1 is that in this comparative example, the gas-atomized iron-nickel powder with a D50 of 15 μm (i.e., the material to be used as the center column) used in step (1-1) of step (1) of Example 1 is replaced with a gas-atomized iron-silicon material with a D50 of 20 μm. The other steps and parameters are the same as those in Example 1.
[0025] Comparative Example 6 The difference between this comparative example and Example 1 is that the heat treatment process used in step (2) of this comparative example is to raise the temperature from room temperature to 720° C. and keep the temperature for 60 minutes. The other steps and parameters are the same as those in Example 1.
[0026] Example 2 This embodiment relates to a method for preparing a one-piece molded inductor with a negative temperature coefficient of loss characteristics, comprising the following steps: (1) Preparation of two soft magnetic metal powders: (1-1) Passivation: 100 g of carbonyl iron powder with a D50 of 10 μm was added with a suspension prepared by adding 0.3 g of phosphoric acid, 0.5 g of aluminum zinc phosphomolybdate, 0.2 g of manganese zinc ferrite powder with a D50 of 1 μm, and 20 g of distilled water, and the mixture was stirred for passivation. After drying, the passivated carbonyl iron powder was obtained. 100 g of aerosolized iron-nickel powder with D50=15 μm was added with a suspension prepared by 0.3 g of phosphoric acid, 0.4 g of aluminum zinc phosphomolybdate, 0.2 g of manganese zinc ferrite powder with D50=1 μm, 0.2 g of chromic acid, and 20 g of distilled water, and stirred for passivation, and dried to obtain a passivated aerosolized iron-nickel powder; (1-2) Coating: using a coating solution containing 0.8 g of phenylchlorosilane, 0.8 g of methylchlorosilane, 3.2 g of silicone resin, 0.3 g of silane coupling agent, and 10 g of acetone solution, the passivated carbonyl iron powder and the passivated atomized iron-nickel powder are respectively coated to obtain coated carbonyl iron powder and coated atomized iron-nickel powder; (1-3) Granulation: The coated carbonyl iron powder is granulated into 60 mesh, and the coated aerosolized iron-nickel powder is granulated into 100 mesh; (1-4) Adding lubricant: 0.4 g of stearic acid lubricant is mixed evenly with the granulated carbonyl iron powder to obtain treated carbonyl iron powder; 0.4 g of stearic acid lubricant is mixed evenly with the granulated aerosolized iron-nickel powder to obtain treated aerosolized iron-nickel powder; (2) Preparation of the one-piece molded inductor center column: The treated gas atomized iron-nickel powder is used to press the middle column for the one-piece inductor, the diameter of the middle column is 4.98mm, the height is 4.0mm, the use pressure is 2200MPa, and heat treatment is performed. The heat treatment curve is that the first stage insulation temperature is 380℃, the insulation time is 30min; the second stage insulation temperature is 540℃, the insulation time is 25min; the third stage insulation temperature is 630℃, the insulation time is 40min; the fourth stage insulation temperature is 730℃, the insulation time is 70min, and finally cooled to room temperature with the furnace; (3) Using the coating liquid prepared in step (1), the middle column obtained in step (2) is bonded to the center of the integrally formed inductor coil, wherein the coil specification wire diameter is 1.0 mm, the coil diameter is 5.0 mm, and the number of coil turns is 5.5 turns; (4) The coil bonded in step (3) is embedded in the carbonyl iron powder treated in step (1), and a 1250 series inductor product is pressed at a pressure of 2000 MPa, i.e., an integrated inductor with a length of 12.0 mm, a width of 12.0 mm, and a height of 5.0 mm. After pressing, the product is baked. During the baking process, the first stage is to heat the product to 120° C. for 20 minutes and keep the temperature for 30 minutes; the second stage is to heat the product to 180° C. for 20 minutes and keep the temperature for 150 minutes, and then cool the product to room temperature in the furnace.
[0027] Comparative Example 7 The difference between this comparative example and Example 2 is that in this comparative example, the carbonyl iron powder with D50=10μm and the atomized iron-nickel powder with D50=15μm used in step (1-1) of step (1) of Example 2 are all replaced with sendustine powder with D50=30um (that is, the column material and the embedded material in this comparative example are both sendustine powder). The other steps and parameters are the same as those in Example 2.
[0028] Comparative Example 8 The difference between this comparative example and Example 2 is that in this comparative example, the carbonyl iron powder with D50=10μm and the atomized iron-nickel powder with D50=15μm used in step (1-1) of step (1) of Example 2 are all replaced with atomized iron-silicon powder with D50=30um (that is, the column material and the embedded material in this comparative example are both atomized iron-silicon powder). The other steps and parameters are the same as those in Example 2.
[0029] Comparative Example 9 The difference between this comparative example and Example 2 is that the passivation agent used in the passivation treatment in step (1-1) of step (1) of this comparative example is only a solution containing 0.6 g of magnesium oxide powder and 20 g of distilled water. The other steps and parameters are the same as those of Example 2.
[0030] Comparative Example 10 The difference between this comparative example and Example 2 is that the coating liquid in step (1-2) of step (1) of this comparative example is 4.2 g of epoxy resin and 0.9 g of epoxy resin curing agent. The other steps and parameters are the same as those of Example 2.
[0031] Comparative Example 11 The difference between this comparative example and Example 2 is that the amount of each raw material in the suspension during passivation in step (1-1) of step (1) of this comparative example is twice that of Example 2, that is, in this comparative example: 100g of carbonyl iron powder with D50=10μm was added with 0.6g phosphoric acid, 1.0g aluminum zinc phosphomolybdate, 0.4g D50=1μm manganese zinc ferrite powder, and 20g distilled water, and the mixture was stirred and passivated, and the passivated carbonyl iron powder was obtained after drying; 100g of aerosolized iron-nickel powder with D50=15μm was added with 0.6g phosphoric acid, 0.8g aluminum zinc phosphomolybdate, 0.4g D50=1μm manganese zinc ferrite powder, 0.4g chromic acid, and 40g distilled water, and the mixture was stirred and passivated, and the passivated aerosolized iron-nickel powder was obtained after drying. The other steps and parameters were the same as those in Example 2.
[0032] Comparative Example 12 The difference between this comparative example and Example 2 is that the amount of each raw material in the coating solution in step (1-2) of step (1) of this comparative example is twice that of Example 2, that is, in this comparative example: Use a coating liquid containing 1.6g of phenylchlorosilane, 1.6g of methylchlorosilane, 6.4g of silicone resin, 0.6g of silane coupling agent, and 10g of acetone solution to coat the passivated carbonyl iron powder and the passivated atomized iron-nickel powder, respectively, to obtain coated carbonyl iron powder and coated atomized iron-nickel powder.
[0033] The other steps and parameters are the same as those in Example 2.
[0034] Performance measurement and analysis: For an integrally formed inductor device, the conversion efficiency at different temperatures can be used to measure the loss characteristics. Therefore, the loss characteristics are characterized by testing the conversion efficiency of the inductors obtained in the embodiment and the comparative example.
[0035] The inductance value is measured at a frequency of 100kHz. The conversion efficiency is measured at a frequency of 50kHz and a magnetic induction intensity of 100mT at 25℃ / 100℃. The characteristic test results of Example 1 and Comparative Examples 1-6 are shown in Table 1; the characteristic test results of Example 2 and Comparative Examples 8-11 are shown in Table 2; Table 1: Property test results of Example 1 and Comparative Examples 1-6 It can be seen from Table 1 that the middle column pressed by atomized iron-nickel powder and the product pressed by carbonyl iron powder can effectively improve the inductance and efficiency of the product, and the efficiency is higher than 25°C under 100°C. By changing the middle column material, passivator, heat treatment process, etc., the inductance of the one-piece molded inductor is significantly reduced, and the conversion efficiency at high temperature is also significantly weaker than that of Example 1. Therefore, the one-piece molded inductor prepared by the formula and process conditions of the present invention has the advantages of high inductance and negative temperature coefficient of loss. The use of metal powders such as pure carbonyl iron, iron silicon chromium, iron silicon, and iron silicon aluminum not only fails to achieve the goal of high inductance due to the low overall density, but also because the middle column material does not have a negative temperature coefficient of loss, resulting in low high-temperature conversion efficiency. The low surface insulation resistance of the powder caused by the change of the passivator or the high loss caused by improper heat treatment process are also important reasons for the low conversion efficiency.
[0036] Table 2: Property test results of Example 2 and Comparative Examples 7-10 According to Table 2, only the mixed use of aerosolized iron-nickel powder and carbonyl iron powder has a better effect. It is difficult to achieve the effect of high inductance and negative temperature coefficient of loss by using only magnetic powder core materials. As for the passivation and coating of powders, ordinary metal oxides or epoxy resins that cannot withstand high temperatures are difficult to achieve the purpose of low loss after heat treatment, so they show relatively low conversion efficiency. If the amount of suspension used during passivation or coating liquid used during coating is large, the magnetic permeability will be reduced and then the inductance value will be reduced, while the hysteresis loss will increase, thereby reducing the conversion efficiency.
[0037] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for preparing a one-piece molded inductor with a negative temperature coefficient of loss characteristics, characterized in that: The following steps are involved: (1) Preparation of soft magnetic metal powder: The carbonyl iron powder and the atomized iron-nickel powder are respectively subjected to passivation, coating, granulation and lubricant addition treatment to obtain two soft magnetic metal powders: the treated carbonyl iron powder and the treated atomized iron-nickel powder, which are used for standby; (2) Preparation of the one-piece molded inductor center column: The treated gas-atomized iron-nickel powder is pressed to form the center column of the one-piece molded inductor, and then heat-treated; (3) Bonding the center column into the coil; (4) The coil bonded in step (3) is embedded in the treated carbonyl iron powder, pressed into shape and baked to obtain a product.
2. The preparation method according to claim 1, characterized in that In the step (1), the specific processing methods of passivation, coating, granulation and adding lubricant are: (1-1) Passivation: The carbonyl iron powder is passivated by using suspension A; the atomized iron-nickel powder is passivated by using suspension B; The suspension A comprises: phosphoric acid, aluminum zinc phosphomolybdate, manganese zinc ferrite powder and distilled water; The suspension B comprises: phosphoric acid, aluminum zinc phosphomolybdate, manganese zinc ferrite powder, chromic acid and distilled water; (1-2) Coating: The coating liquid used during coating is: an acetone solution containing phenylchlorosilane, methylchlorosilane, silicone resin, and a silane coupling agent; (1-3) Granulation: The coated carbonyl iron powder is granulated into 60 mesh, and the coated aerosolized iron-nickel powder is granulated into 100 mesh; (1-4) Adding lubricant: The lubricant is mixed evenly with the granulated carbonyl iron powder and the granulated atomized iron-nickel powder to obtain treated carbonyl iron powder and treated atomized iron-nickel powder.
3. The preparation method according to claim 2, characterized in that: In step (1-1) of step (1), in the suspension A, the mass of phosphoric acid is 0.1-0.3% of the mass of the carbonyl iron powder, the mass of aluminum zinc phosphomolybdate is 0.3-0.5% of the mass of the carbonyl iron powder, the mass of manganese zinc ferrite powder is 0.1-0.2% of the mass of the carbonyl iron powder, and the mass of distilled water is 15-30% of the mass of the carbonyl iron powder; In suspension B, the mass of phosphoric acid is 0.1-0.3% of the mass of the atomized iron-nickel powder, the mass of aluminum zinc phosphomolybdate is 0.3-0.5% of the mass of the atomized iron-nickel powder, the mass of manganese zinc ferrite powder is 0.1-0.2% of the mass of the atomized iron-nickel powder, the mass of chromic acid is 0.1-0.2% of the mass of the atomized iron-nickel powder, and the mass of distilled water is 15-30% of the mass of the atomized iron-nickel powder.
4. The preparation method according to claim 2, characterized in that: In step (1-1) of step (1), the mass ratio of carbonyl iron powder to atomized iron-nickel powder is 1:1; the particle size of carbonyl iron powder is D50=10 μm, the particle size of atomized iron-nickel powder is D50=15 μm; and the particle size of manganese-zinc ferrite powder is D50=1 μm.
5. The preparation method according to claim 2, characterized in that: In step (1-2) of step (1), when the passivated carbonyl iron powder is coated, in the coating solution, the mass of phenylchlorosilane is 0.5-0.8% of the mass of the carbonyl iron powder, the mass of methylchlorosilane is 0.4-1.0% of the mass of the carbonyl iron powder, the mass of the silicone resin is 2.3-3.5% of the mass of the carbonyl iron powder, and the mass of the silane coupling agent is 0.2-0.3% of the mass of the carbonyl iron powder; the mass of the acetone solution is 8-10% of the mass of the carbonyl iron powder; When the passivated atomized iron-nickel powder is coated, in the coating liquid, the mass of phenylchlorosilane is 0.5-0.8% of the mass of the atomized iron-nickel powder, the mass of the methylchlorosilane is 0.4-1.0% of the mass of the atomized iron-nickel powder, the mass of the silicone resin is 2.3-3.5% of the mass of the atomized iron-nickel powder, and the mass of the silane coupling agent is 0.2-0.3% of the mass of the atomized iron-nickel powder; the mass of the acetone solution is 8-10% of the mass of the atomized iron-nickel powder.
6. The preparation method according to claim 2, characterized in that: In step (1-4) of step (1), the lubricant is any one or more of magnesium stearate, zinc stearate, stearic acid, and paraffin powder; when the lubricant is added to the granulated carbonyl iron powder, the mass of the lubricant is 0.3-0.4% of the mass of the carbonyl iron powder; When the lubricant is added to the granulated atomized iron-nickel powder, the mass of the lubricant is 0.3-0.4% of the mass of the atomized iron-nickel powder.
7. The preparation method according to claim 1, characterized in that: In the step (2), the pressing pressure is 1800-2200 MPa; the diameter and height of the middle column after pressing are smaller than the coil, so that the middle column is bonded to the center of the coil; the middle column after pressing is heat treated in a hydrogen atmosphere; in the step (3), the coating liquid used during coating is used for bonding.
8. The preparation method according to claim 7, characterized in that: In the step (2), the heat treatment process includes four insulation stages: the insulation temperature of the first stage is 350-380°C, and the insulation time is 20-30 minutes; the insulation temperature of the second stage is 520-540°C, and the insulation time is 20-30 minutes; the insulation temperature of the third stage is 600-630°C, and the insulation time is 30-50 minutes; the insulation temperature of the fourth stage is 720-730°C, and the insulation time is 50-70 minutes, and finally the furnace is cooled to room temperature.
9. The preparation method according to claim 1, characterized in that: In the step (4), the pressing pressure is 1800-2200 MPa; the baking process includes two stages: the first stage is to heat up to 120°C for 20 minutes and keep warm for 30 minutes; the second stage is to heat up to 180°C for 20 minutes and keep warm for 150 minutes, and finally cool to room temperature in the furnace.
10. A one-piece molded inductor with a negative temperature coefficient of loss characteristics, characterized in that: The loss characteristic negative temperature coefficient one-piece molded inductor is prepared by the preparation method described in any one of claims 1-9.
Citation Information
Patent Citations
Preparation method of high-frequency and high-efficiency integrated inductor
CN114373626A
High-performance iron-nickel soft magnetic powder core and preparation method thereof
CN118629739A
Soft magnetic composite metal material for integrally formed inductor and preparation method of soft magnetic composite metal material
CN118800543A
Magnetic composite material and preparation method therefor, and inductor and manufacturing method therefor
WO2022077150A1
Method for manufacturing integrally formed inductor, and inductor prepared by applying same
WO2023133994A1
Cited By
Preparation and application of small magnetic powder core with high-flux magnetic ring performance
CN119852079A